Problems and features of intelligent design of roofs/Intelektinio projektavimo problemos ir ypatybės renovuojant stogus - Makutėnienė, Daiva; Čiupaila, Lionginas (Journal of Civil Engineering and Management, 1999)
Intelligent computer-aided design is impossible without the object of design, component parts, participants of the process and analysis of their relations. The control of these relations was performed without computer. Therefore the processes flew without optimal criteria and technics of optimisation. Renovation of a building will depend on three most important concerned groups involved in the process: – customers; – designing organisations; – building and constructing organisations. The entire process of design – from the idea to complete documentation – must be planned and executed with consideration of goals aspired by the interested parties – customers, designers and construction organisations. This process should realise the cycles of design, co-ordination and expertise of final solution. There are one-stage or two-stage design processes in traditional design process (Fig 2). Development of the project by one or two stages is pointed out by the design task of customer and depends upon technical complexity of the object. Complex objects are designed by a two-stage design process. One-stage design (Fig 3) is used, when the object is not complicated and includes many typical constructions. A great deal of graphics, economical data, accepted standards, rules are used in today's design process. While designing a building, the information flow could be controlled with the help of intelligent systems of design. Some information systems can be applied to different parts of a building. Fig 4 represents the structure of information system for roof design. Any part of information system is a complex object. Parts of information system for roof design are related to graphical-geometrical information. Relations between elements of roof intelligent design system are represented in Fig 5. Structure of some elements of information system (Fig 6) and internal relations are complex and manifold, so managing is possible only by intelligent design system. During the process of intelligent system design the same participants take part as in the traditional process: customers, design organisations, building and constructing organisations, but the relations between these participants are of a new quality. Fig 7 represents the relations between traditional participants and the flow of up-to-date information. The process of intelligent design differs from the traditional one by the following features: – the intelligent system includes features of traditional design (design, expertise, coordination, renewing), but it is the system of new technology and quality due to the possibility of real optimisation; – the process of renovation of dwelling houses roofs has an important feature, namely, a possibility for the unification of the design process. Rational composition of unificated projects can and must be supported by computer aided graphical and non-graphical databases with possibilities of the intelligent design;– relations between data groups of a design object (Fig 7 – A, B, C and D) can be managed by computer intelligent software.The intelligent process has some problems: – the main stages of the roof design are related to considerations and financial possibilities of customers, aesthetical and architectural evaluation. These stages are related by three main interested groups (customers, design organisations, building and constructing organisations) and other institutions of the government. They can be optimised only by computer at intelligent level; – the problem of information flowing, because methods of presentation of data must be co-ordinated with customers, design organisations, building and constructing organisations. Control techniques must be provided for its managing; – data and knowledge bases must be continuously formed and renewed until using “Internet” and other modern methods for information transmission.Article in Lithuanian.First Published Online: 26 Jul 2012